Justice Collaborator: A Legal Phenomenon Study in the Perspective of Criminal Law and Islamic Jurisprudence - Gunaldi Ahmad; Fitri Mustafa; Munir Waspada; Amita Diananda (STAI Publisistik Thawalib Jakarta, 2026)
This research strengthens justice collaborator policies by integrating maqasid al-shariah values into legal protection and criminal justice practices. This research analyzes justice collaborators in Indonesian and Islamic law, examining alignment with maqasid, legal protection, and social impacts. This study employs qualitative library research with comparative-interdisciplinary approaches, drawing on documentation, interviews, observations, content analysis, triangulation techniques, and a normative examination of Indonesian criminal law, Islamic law, and maqasid al-shariah principles. The findings show that the concept of justice collaborators in Indonesian positive law is legally recognized through SEMA No. 04 of 2011 and functions as an important mechanism for uncovering organized crimes through cooperating offender testimony. From the Islamic law perspective, the concept aligns with maqasid al-shari‘ah, particularly the principles of maslahah, justice, and public welfare. Differences emerge among Islamic schools of thought regarding the acceptance of cooperating offenders as witnesses. The Hanafi school rejects their testimony due to fairness requirements, whereas the Shafi‘i school allows it through repentance and qiyas. Thus, justice collaborators support substantive justice and modern evidentiary development. Justice collaborators strengthen criminal justice systems by integrating legal effectiveness, maqasid al-shari‘ah principles, substantive justice, and public welfare. This research contributes theoretically, practically, and methodologically by integrating Indonesian criminal law and maqasid al-shariah perspectives comprehensively.